2D vs. 3D Numerical Approaches for Fish Habitat Evaluation of a Large River — Is 2D Modeling Sufficient? - Füstös, Vivien; Erős, Tibor; Józsa, János (Periodica Polytechnica Civil Engineering, 2021)
Computational Fluid Dynamics is an effective tool for assessing non-present conditions, thus also in habitat evaluation within ecohydraulics. Deciding whether to apply a one-, two- or three-dimensional numerical approach, is an optimization that needs to be performed by every task, given the capability and the demands of specific approaches. In this paper we compare the utility of two-dimensional (2D) versus three-dimensional (3D) hydrodynamical simulations for ecohydraulic purposes. The basis of the comparation were 1) three simulated abiotic variables: water depth, depth averaged flow velocity and bed material composition, and 2) an overall performance in a meso-scale fish habitat evaluation, based on the simulated three variables. The biotic parameters for the models were the habitat suitability curves of three fish species, the Danube streber (Zingel streber), the round goby (Neogobius melanostomus) and the white bream (Blicca bjoerkna). We found that in terms of ecohydraulic utilization, the 2D approach performed sufficiently to simulate the hydrodynamics of a large river. The errors originating from the 3D-2D simplification yielded negligible differences in habitat evaluation, and the agreement in the habitat suitability indices calculated from the simulated metrics was satisfactory. Henceforth, the theory was turned into an application as we performed habitat mapping on a 100 km long, Hungarian reach of the Danube River, with the abiotic parameters resulting from a 2D hydrodynamical simulation. The possibility of simplifying the approach from 3D to 2D provides a cost-efficient numerical tool at larger scales for ecohydraulic studies, and especially for evaluating habitat suitability of riverine fish.